Guidance for reporting 2020 avian influenza data. Issue 5 (20th May 2020) - ,; Aznar, Inma; Bocca, Valentina; Gibin, Davide; Papanikolaou, Alexandra; Stoicescu, Anca‐Violeta
Abstract : Avian influenza surveillance data should be submitted twice a year from Member States to the European Food Safety Authority (EFSA) using the EFSA Standard Sample Description version 2 (SSD2). Specific guidelines to support reporting countries with this data transmission (using eXtensible Markup Language (XML) data transfer) are given in this report. The objective of this report is to explain in detail the individual data elements that are included in the EFSA (SSD2) data model used for reporting Avian Influenza (AI) surveillance data. These data elements should be used for reporting laboratory testing results via the EFSA Data Collection Framework, and according to the protocol described in the EFSA Guidance on Data Exchange version 2. A full description of the data elements including information about the data type are presented. Further, a list of allowed terms and business rules or requirements that apply are shown.